TRASFORMASI BUDAYA DI ERA DIGITAL - Sumiyanti; Syaifurrohman, Amir; Alfina; Salimu, Salman Alfarisi (Universitas Aisyah Pringsewu, 2025)
The process of cultural transformation that occurred during the internet era represents a major change in the way individuals and society interact with culture and technology. Utilizing various digital platforms such as social media, websites and phone apps, access to cultural information has become easier. To gain a better understanding of the impact of digitalization on culture, this article analyzes the relevant literature. In the modern era, not only has preserving and expressing culture become possible, but it also presents challenges such as cultural commodification and erosion of local identity. Digitization allows documentation of endangered traditions and a space for artists to speak to audiences spread across the globe. However, issues such as the digital divide and privacy issues in global social interactions may have to be considered. In the digital era, cultural transformation reflects major changes in the way individuals and societies interact with technology. Therefore, the aim of this article is to provide insight into how cultural transformation occurs in a digital context and how this transformation shapes modern society and technology with today's technological advances.